Fibra em detergente neutro na ração de leitões: Desempenho e implicações gastrointestinais - Nepomuceno, Rafael Carlos; Watanabe, Pedro Henrique; Freitas, Ednardo Rodrigues; de Carvalho, Luiz Euquerio; de Oliveira, Emanuela Lima; Veira, Alini Mari [UNESP] (FapUNIFESP (SciELO), 2016)
The intestinal health of piglets depends on the balance between diet, microflora and mucosal integrity. Disruption of this balance can compromise the digestive functions, leading to diarrhoeal frame and decline in performance of piglets. However, the level and type of fibre can limit digestive disorders. Thirty newly weaned piglets were used to evaluate the levels of neutral detergent fibre (NDF) in diets regarding performance, pH, viscosity and concentration of short chain fatty acids of digestive contents, gastrointestinal transit time, morphology of the intestinal mucosa, weights of organs and occurrence of diarrhoea. NDF level had quadratic effect on weight gain and feed conversion ratio of piglets, estimating best results at the level of 10.4%. NDF level had no effect on the pH, viscosity and concentration of short chain fatty acids. NDF levels below 10.2% or above 13.5% reduced the transit time of digesta. There was quadratic effect on villus height in the duodenum and jejunum and in the crypt depth of jejunum. There was linear increase in stomach, caecum and colon weights and linear decrease in the occurrence of diarrhoea according to increasing NDF levels. It is concluded that levels below 10.2% and above 13.5% reduce the transit time of digesta, whereas 12.2% NDF level results in better mucosa structure of the small intestinal, with an increase in the weights of the stomach, caecum and colon and a reduction in the occurrence of diarrhoea with increasing NDF level in diets, resulting in better performance of weaned piglets with 10.4% of NDF.
Neutral detergent fibre in piglet diets: Performance and gastrointestinal implications
Keywords: Pigs; Short chain fatty acids; Transit time; Viscosity